1995
DOI: 10.1007/bf02787910
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme mimics as catalytic antisense reagents

Abstract: Viral and fungal infections and some cancers may be described as diseases that are characterized by the expression of certain unwanted proteins. They could be termed induced genetic disorders, with induction provided by mutation or infection. A comprehensive method to inactivate injurious genes based on their nucleic acid sequences has the potential to provide effective antiviral and anticancer agents with greatly reduced side effects. We describe a chemical approach to such gene-specific pharmaceutical agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The chimeric ribo/2Ј-O-methylribooligonucleotides (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were synthesised from commercial 2Ј-O-methylated (Glenn Research) and 2Ј-O-[1-(2-fluorophenyl)-4-methoxypiperidin-4-yl] (2Ј-O-Fpmp) protected (Cruachem) building blocks by a conventional phosphoramidite strategy, according to the standard RNA-coupling protocol of ABI 392 DNA/RNA Synthesizer. The protecting groups were removed and the crude oligonucleotides were purified as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chimeric ribo/2Ј-O-methylribooligonucleotides (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were synthesised from commercial 2Ј-O-methylated (Glenn Research) and 2Ј-O-[1-(2-fluorophenyl)-4-methoxypiperidin-4-yl] (2Ј-O-Fpmp) protected (Cruachem) building blocks by a conventional phosphoramidite strategy, according to the standard RNA-coupling protocol of ABI 392 DNA/RNA Synthesizer. The protecting groups were removed and the crude oligonucleotides were purified as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The development of sequence-selective RNA cleaving reagents, artificial RNases, has attracted considerable attention over the last decade. [1][2][3][4][5][6] It is hoped that these cleaving agents will offer novel methods to treat viral infections, cancer, hereditary diseases or antibiotic-resistant bacterial infections. The general concept for the design of such agents is simple: an oligonucleotide recognises the target RNA sequence by hybridisation and its catalytically active function, once attached, induces a chemical modification that inactivates the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Arti®cial hydrolases based on main-group, lanthanide or transition metal complexes have been developed as nonenzymatic alternatives for the hydrolysis of the phosphodiester bonds in DNA and RNA (Chin, 1991;Kim & Suh, 1994;Williams & Chin, 1996;Williams et al, 1999). It has been suggested that such catalysts may have a signi®cant future impact in gene-cloning, gene-mapping, or therapeutics (Bashkin et al, 1995;Komiyama & Sumaoka, 1996;Hegg & Burstyn, 1998;Komiyama et al, 1999). Cobalt(III), with its high charge density, is a potent candidate for use in hydrolysing phosphodiesters; for example, recently published values for DNA cleavage show that Co III complexes have rate constants of around 2 Â 10 4 s À1 , which is about three times higher than that for europium(III) salts (Hettich & Schneider, 1997).…”
Section: Commentmentioning
confidence: 99%
“…Catalytic RNA is also a very good method for development of specific catalysts within its limited substrate range. Clever applications of specific RNA hydrolysis are currently being applied to medical problems (93)(94)(95). By contrast, the de novo techniques have yielded few breakthroughs of practical value.…”
mentioning
confidence: 99%